Impact of Obesity on Influenza A Virus Pathogenesis, Immune Response, and Evolution - Honce, Rebekah; Schultz-Cherry, Stacey (Frontiers in Immunology, 2019)
With the rising prevalence of obesity has come an increasing awareness of its impact on communicable disease. As a consequence of the 2009 H1N1 influenza A virus pandemic, obesity was identified for the first time as a risk factor for increased disease severity and mortality in infected individuals. Over-nutrition that results in obesity causes a chronic state of meta-inflammation with systemic implications for immunity. Obese hosts exhibit delayed and blunted antiviral responses to influenza virus infection, and they experience poor recovery from the disease. Furthermore, the efficacy of antivirals and vaccines is reduced in this population and obesity may also play a role in altering the viral life cycle, thus complementing the already weakened immune response and leading to severe pathogenesis. Case studies and basic research in human cohorts and animal models have highlighted the prolonged viral shed in the obese host, as well as a microenvironment that permits the emergence of virulent minor variants. This review focuses on influenza A virus pathogenesis in the obese host, and on the impact of obesity on the antiviral response, viral shed, and viral evolution. We comprehensively analyze the recent literature on how and why viral pathogenesis is altered in the obese host along with the impact of the altered host and pathogenic state on viral evolutionary dynamics in multiple models. Finally, we summarized the effectiveness of current vaccines and antivirals in this populations and the questions that remain to be answered. If current trends continue, nearly 50% of the worldwide population is projected to be obese by 2050. This population will have a growing impact on both noncommunicable and communicable diseases and may affect global evolutionary trends of influenza virus.